DETEKSI TEMU RUAS DAUN SIRIH MENGGUNAKAN ALGORITMA THINNING - Tanjung, Tia; Novel., Kadinar (LPPM Universitas Nusa Mandiri, 2017)
Society is still a lot need the best solution to select an appropriate treatment to address a variety of perceived grievances, from medical treatment to the treatment of non-medical or often called traditional medicine, betel leaves as one of the plants that are useful to be a cure for certain diseases and betel leaves public trust to be used as a treatment appointment is betel leaf segments. Processing betel leaves on a large scale is needed to determine the ease of retrieval of betel leaf segments. The purpose of the research is to utilize image processing algorithms thinning. The method used consists of betel leaf image acquisition, image changes to a grayscale, edge detection comprising Prewitt, Robert, Sobel and thinning. Furthermore, the analysis of the results of research showing the most thinning algorithm is good to get that appointment betel segment.